Peningkatan pengetahuan “Pentingnya personal hygiene organ reproduksi wanita serta praktik penerapannya” pada ibu dan remaja putri di Kelurahan Mojo Surabaya - Purbowati, Rini; Tri Ratnasari , Diana; Soekanto, Ayly; Tjandra, Lusiani; Masfufatun, Masfufatun; Indahsari, Noer Kumala (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Infectious and deadly diseases caused by bacterial infection are currently still a global problem, one of which is Bacterial Vaginosis (BV) infection. Following polymicrobial as a result of changes in normal hydrogen peroxide produced by Lactobacillus spp in the vagina. One of the triggering factors for BV is the practice of